MFS Transporters and GABA Metabolism Are Involved in the Self-Defense Against DON in Fusarium graminearum - Wang, Qinhu; Chen, Daipeng; Wu, Mengchun; Zhu, Jindong; Jiang, Cong; Xu, Jin-Rong; Liu, Huiquan (Frontiers in Plant Science, 2018)
Trichothecene mycotoxins, such as deoxynivalenol (DON) produced by the fungal pathogen, Fusarium graminearum, are not only important for plant infection but are also harmful to human and animal health. Trichothecene targets the ribosomal protein Rpl3 that is conserved in eukaryotes. Hence, a self-defense mechanism must exist in DON-producing fungi. It is reported that TRI (trichothecene biosynthesis) 101 and TRI12 are two genes responsible for self-defense against trichothecene toxins in Fusarium. In this study, however, we found that simultaneous disruption of TRI101 and TRI12 has no obvious influence on DON resistance upon exogenous DON treatment in F. graminearum, suggesting that other mechanisms may be involved in self-defense. By using RNA-seq, we identified 253 genes specifically induced in DON-treated cultures compared with samples from cultures treated or untreated with cycloheximide, a commonly used inhibitor of eukaryotic protein synthesis. We found that transporter genes are significantly enriched in this group of DON-induced genes. Of those genes, 15 encode major facilitator superfamily transporters likely involved in mycotoxin efflux. Significantly, we found that genes involved in the metabolism of gamma-aminobutyric acid (GABA), a known inducer of DON production in F. graminearum, are significantly enriched among the DON-induced genes. The GABA biosynthesis gene PUT2-2 (PROLINE UTILIZATION 2-2) is down-regulated, while GABA degradation genes are up-regulated at least two-fold upon treatment with DON, resulting in decreased levels of GABA. Taken together, our results suggest that transporters influencing DON efflux are important for self-defense, and that GABA mediates the balance of DON production and self-defense in F. graminearum.